Quanto pricing beyond Black-Scholes - Holger Maria Fink; Stefan Mittnik (Journal of Risk and Financial Management, 2021)
Since their introduction, quanto options have steadily gained popularity. Matching Black-Scholes-type pricing models and, more recently, a fat-tailed, normal tempered stable variant have been established. The objective here is to empirically assess the adequacy of quanto-option pricing models. The validation of quanto-pricing models has been a challenge so far, due to the lack of comprehensive data records of exchange-traded quanto transactions. To overcome this, we make use of exchange-traded structured products. After deriving prices for composite options in the existing modeling framework, we propose a new calibration procedure, carry out extensive analyses of parameter stability and assess the goodness of fit for plain vanilla and exotic double-barrier options.
Keywords: 330; calibration; Lévy process; Nikkei 225; normal tempered stable process; parameter stability; quanto options